Anatomical Brain Changes and Cognitive Abilities in Patients with Obstructive Sleep Apnea Syndrome and Nonalcoholic Fatty Liver Disease. (20th October 2021) - Filipovic, Branka; Đuric, Vesna; Filipovic, Natasa; Kiurski, Stanimir; Al Kiswani, Jamal; Markovic, Branka; Laketic, Darko; Marjanovic-Haljilji, Marija; Kapor, Slobodan; Filipovic, Branislav R.
Abstract : Obstructive sleep apnea (OSA) is characterized by repetitive complete or partial collapse of the upper airway and reduction of airflow during sleep. It is associated with significantly increased daytime muscle sympathetic nerve activity thought to result from the repetitive intermittent periods of hypoxemia during sleep and brain alterations that are likely to result. Different brain regions are affected by subsequent hypoxia/anoxia. Neurodegenerative processes result in measurable atrophy of cortical gray matter in the temporal lobes and posterior cingulate cortex, as well as in subcortical structures such as the hippocampus, amygdala, and thalamus. This study involved a group of firstly diagnosed, therapy- naive, nonalcoholic fatty liver disease (NAFLD) patients, out of which 144 (96 males and 48 females), aged 34–57 (mean 47.88 ± 6.07), satisfied the recruiting criteria for the study and control groups. All the patients underwent MRI scanning, polysomnography testing, and cognitive evaluation. Cognitively, worse results were obtained in the group with OSA (p < 0.05 ) and NAFLD (p = 0.047 ). A significant decrease in volumes of cortical and subcortical structures was revealed (p < 0.001 ). In conclusion, brain deterioration followed by cognitive impairment is, most likely, the result of intermittent hypoxia and anoxia episodes that initiate the domino process of deteriorating biochemical reactions in the brain.